Lei de introdução às normas do direito brasileiro: o sentido constitucionalmente adequado de observar as consequências práticas decisões administrativa e judicial - Lima, Italo Vasconcelos Sousa (Universidade do Vale do Rio dos Sinos, 2022)
The present work analyzes the changes that the Law of Introduction to the Norms of Brazilian Law - LINDB has undergone. Through Law No. 13.655/2018, 10 articles were inserted in the text of LINDB, among which is article 20, which is the focus of this work, determining that administrative, judicial and controlling decisions will not be decided based on values abstract legal frameworks without considering the practical consequences of the decision. This article raises a series of questions, ranging from an understanding of what it actually means to consider practical consequences, how they should be considered and to what extent they should be considered, as well as what other elements must be present in order for them to be considered. can actually reach a correct decision. In addition to the provision brought by LINDB, the Constitution itself already establishes the duty to state reasons, which is present in art. 93, IX. Thus, aiming to develop points that contribute to a debate around the positive changes in LINDB, the present work is divided into three parts: in the first chapter, we sought to characterize the path of LINDB, from the Law of Introduction to the Civil Code to the to the changes promoted through Law No. 13,655, then, we sought to analyze the consequentialism present in art. 20 from LINDB; consequentialism was also analyzed, and a debate was held with Ronald Dworkin's theory of right as integrity. In the second chapter, the reconstruction of some points of the “second debate” between Richard Posner and Ronald Dworkin was carried out. This debate is important because it brings points that help in understanding the analysis of consequences in decisions. While Posner has a view from pragmatism, Dworkin carries out a harsh critique of pragmatism, and, among other points, defends the role of principles in the assessment of consequences. Not that the analysis of consequences is something that the decision should completely depart from, but, as Dworkin will demonstrate, the principles are fundamental so that the consequences do not reflect something merely personal. The third chapter sought to delimit the bases for an understanding of the constitutionally adequate response, built by Streck. Likewise, the reading of art. 20 of LINDB through the conjugation of art. 489, §1 of the CPC, together with art. 93, IX of the Federal Constitution, in order to enable a correct understanding of consequentialism in legal decisions.
Keywords: LINDB; Consequencialismo; Direito como integridade; Resposta constitucionalmente adequada; Consequentialism; Law as integrity; Constitutionally adequate response; ACCNPQ::Ciências Sociais Aplicadas::Direito